2019
DOI: 10.1080/21681376.2019.1643777
|View full text |Cite
|
Sign up to set email alerts
|

House price affordability, the global financial crisis and the (ir)relevance of mortgage rates

Abstract: Although house prices and wages are both influenced by distinct factors that shape their own evolutions, they are also intrinsically connected through house price affordability. Further, macroeconomic policies centred around adjustments in the mortgage rate are of prime importance in ensuring that the housing market does not overheat. This study contributes to the understanding of the link between housing market affordability and mortgage rates by investigating this association across regions of New Zealand us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The case of Auckland is important given the city is the commercial heart of New Zealand and has the greatest proportion of residents. At a regional scale for the focus of this study, more technical analysis has demonstrated that HPA has no statistically significant correlation with mortgage rates in a period of continued low interest rates (Squires and Webber, 2019).…”
Section: Ijhma 153mentioning
confidence: 93%
“…The case of Auckland is important given the city is the commercial heart of New Zealand and has the greatest proportion of residents. At a regional scale for the focus of this study, more technical analysis has demonstrated that HPA has no statistically significant correlation with mortgage rates in a period of continued low interest rates (Squires and Webber, 2019).…”
Section: Ijhma 153mentioning
confidence: 93%
“…This paper focuses attention on the supply of affordable housing for those households that have demand at various levels of affordability. Squires and Webber (2019) demonstrate that 'affordable housing' units may still be far from reaching affordability levels for many residents, particularly in a highly unaffordable city. Sirmans and Macpherson (2003) demonstrate that much of the literature on affordable housing identifies the main problem as being the provision of adequate housing for extremely low-income households.…”
Section: Affordable Housing and Brownfield Developmentmentioning
confidence: 94%
“…These findings were consistent to those of [9,27] that houses in desired places were highly priced and that low income earners were unable to afford and this led them to live in places that they did not fully desire due to financial constraints. Similarly, [20,30] reported negative correlation between desired place of living and the actual place of living and thus indicating that most of low income individuals lived in places they did not fully desired to lack of financial capacity to afford rent for houses in desired places. From the interview, it was evident that most low income individuals cannot be able to afford houses in their most preferred locality due to high prices of the houses.…”
Section: Affordability Of Housingmentioning
confidence: 99%